Integrated Marketing Communication Pada Usaha Industrial Internet of Things - Machine Vision - Monika Teguh; Aulialukita Niantiara; Andrea Hartansa (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
In this era, the Indonesian government is committed to increase Indonesia competitiveness position towards other countries. To achieve this goal, the Ministry of Industry spur domestic industries to innovate in the face of Industry 4.0. One company that answers this challenge is Machine Vision that focuses on Industrial Internet of Things. It optimizes modernizes, and digitizes the Indonesian industry to help companies grow, maximize productivity, and promote efficiency in business processes. This new and unique type of business has difficulties that must be overcome, where it must be able to penetrate an unusual market. Therefore, this study discussed the strategy of Integrated Marketing Communication (IMC) conducted by Machine Vision. This study uses qualitative descriptive research methods with structured interview data collection techniques. The results of this study are, IMC strategy has been contributed positively to Machine Vision with the division of two groups, namely primary and secondary. The positive impact was assessed from the existence of repeat customers and client interest in content on Machine Vision’s social media. But aside from those positive effects, also found several threats in the future.